Plasma amino acids in four models of experimental liver injury in rats - Holeček, M; Mráz, J; Tilšer, I (Amino acids, 1996)
We studied the plasma amino acid profiles in four models of hepatic injury in rats. In partially hepatectomized rats (65% of liver was removed) we observed significant increase of aromatic amino acids (AAA; i.e. tyrosine and phenylalanine), taurine, aspartate, threonine, serine, asparagine, methionine, ornithine and histidine. Branched-chain amino acids (BCAA; i.e. valine, leucine and isoleucine) concentrations were unchanged. In ischemic and carbon tetrachloride acute liver damage we observed extreme elevation of most of amino acids (BCAA included) and very low concentration of arginine. In carbon tetrachloride induced liver cirrhosis we observed increased levels of AAA, aspartate, asparagine, methionine, ornithine and histidine and decrease of BCAA, threonine and cystine. BCAA/AAA ratio decreased significantly in partially hepatectomized and cirrhotic rats and was unchanged in ischemic and acute carbon tetrachloride liver damage. We conclude that a high increase of most of amino acids is characteristic of fulminant hepatic necrosis; decreased BCAA/AAA ratio is characteristic of liver cirrhosis; and decrease of BCAA/AAA ratio may not be used as an indicator of the severity of hepatic parenchymal damage.